Formulation And Characterization Of Palm Oil Esters Based Nano-Cream For Topical Delivery Of Piroxicam: Study Of In Vitro Release And In Vivo Anti-Inflammatory And Analgesic Effects - Abdulkarim, Muthanna F. (2010)

(untitled)
During recent years, there has been increased interest in the use of topical vehicle systems that could assist drug permeation through the skin. The drugs of interest usually those causing or having problems when given orally, e.g., easily hydrolyzed in the gastro-intestinal tract, poor bioavailability or to cause adverse reactions. One such drug is piroxicam, a highly effective anti-inflammatory, anti-pyretic and analgesic but causes gastro-intestinal ulcers and bleeding. One of the most promising vehicle systems for trans-dermal permeation of drugs is a nano-cream, a semisolid emulsion with droplet size of 20-200 nm. The main purpose of this study is to formulate a novel nano-cream containing piroxicam for topical delivery and to use palm oil esters (POEs) a new derrivetised palm oil as the oil phase. In the initial study, pseudoternary phase diagrams of water, POEs and non-ionic surfactant mixture of several HLB values were constructed and several promising nano-cream formulae were selected. The stability under different temperatures and other properties of the formulations including the rheological behaviour, zeta potential, droplet size and structural characteristics of the formulation and Solubility and partition coeffecient of piroxicam were studied.